Maintaining the survival of Malaysian SMEs during covid-19 outbreak: challenges and suggestion for management / Amizahanum Adam, Roshidi Hassan and Hasnida Abdullah - Adam, Amizahanum; Hassan, Roshidi; Abdullah, Hasnida (Universiti Teknologi MARA, 2021)
The Covid-19 pandemic has brought a new phenomenon to human health and development across the globe. This unfavourable scenario is also a trigger to the world economic crisis, after the September 11 attack and the global financial crisis in 2001 and 2008 respectively. The impact of the outbreak has severely affected business owners particularly the small and medium entrepreneurs. This paper provides the setting of those considered as small and medium business organisations. Due to its unique characteristics, precisely in terms of size and capital, these small and medium enterprises are heavily affected in maintaining their businesses and surviving financially. Business challenges include government's policy on movement control order, shortage of cash flow and outdated marketing strategies which make these business owners' struggle to persist during the outbreak. This paper offers a few recommendations to be considered by those entrepreneurs during the period of the pandemic as well as in the recovery process. The suggestions comprise a demand to enhance technology-related skills and knowledge among members of the business, adopting technology as part of business strategy and tools, and engaging a technology-based marketing approach. It is expected that a proper process of transformation in the business operations could help those small and medium entrepreneurs to maintain their survival and sustainability in the market.